Comprehensive evaluation of Epoxy/Li2B4O7 composite for neutron shielding: Experimental characterization and Geant4 simulation analysis - Abady, R. S.; Amro, B. M. S.; Saleh, H.; Alwaheba, Anas; Esaifan, Muayad; Arslan, Halil; Tonguc, Baris T. (Pergamon-Elsevier Science Ltd, 2026)
Epoxy-based composites were prepared by incorporating Li2B4O7 at concentrations ranging from 5 to 30 wt% to enhance neutron shielding performance. To assess the structure, morphology, and particle distribution within the epoxy matrix, scanning electron microscopy (SEM) was used. Experimental measurements with a(252)Cf neutron source at the Jordan Atomic Energy Commission revealed that the composite containing 15 wt% Li2B4O7 exhibited uniform particle distribution and achieved a 20 % improvement in neutron attenuation compared with pure epoxy. Notably, the experimental findings were consistent with Geant4 simulations, thus confirming and validating the simulation model. Furthermore, theoretical and simulation studies indicated that the incorporation of Li2B4O7 improved thermal neutron shielding by similar to 89 % and fast neutron shielding by similar to 8 %, while also reducing the average energy of secondary gamma radiation. Collectively, these results highlight the strong potential of Epoxy/Li2B4O7 composites for advanced neutron shielding applications, including their use as lightweight shielding layers or blocks in neutron facilities, as well as compact shipping containers with superior efficiency compared to conventional materials.
Keywords: Lithium tetraborate; Epoxy composites; Neutron shielding; Inelastic scattering; Neutron absorption; Californium source